Geospatial suitability assessment of small-scale hydropower potential (Dam sites) for green energy in North-Eastern Nigeria - Jimoh A. Ibrahim; Bawuro Ibrahim; Benison Yason; Olabanji O. Aladejana (EQA)
Globally, nations are moving away from the usage of fossil fuels toward cleaner energy sources, hydropower is one of the most significant green energy sources to reduce greenhouse gasses. This study aims to select suitable locations for dam construction in Northeastern Nigeria using geospatial analysis for green energy. The Geographic information system and analytical hierarchy process were used to integrate ten thematics layers: geology, soil, slope, elevation, land use, precipitation, flow accumulation, stream power index, topographic wetness index, and drainage density. To generate a suitability model, ten hydro-physical criteria were used and went through several processing steps. AHP was used to rank and weight each criterion. Five classes were identified from the composite suitability map that was generated: very high, high, moderate, low, and very low. Flow accumulation holds the highest importance, followed by rainfall and drainage density, while slope was the least important in determining the suitability of the region. According to the composite suitability map, roughly 38 % of the region is of the highly suitable category, 54.17 % is moderately suitable while the least was highly suitable class with 0.21 %. Among the six states in the region, Taraba state has the highest potential dam site with three sites while the other has one each except Yobe state with none. Millions of people could have access to green energy by building dams in highly practical and economically viable locations identified. GIS is an effective technique for sustainable dam site location.